A CASE STUDY BASED ON SINGULAR MEDIATION AND REGRESSION MODELS - Zainalabideen AL-Husseini (European Journal of Humanities and Educational Advancements, 2022)
The research aims to study the impact of the Corona virus on the income and psychological state of individuals, as single mediation models were applied with regression models to study and show the effect of the variables under study. The distribution of the various classes came due to its importance to show the size of the impact on the largest possible number of segments of society, and after collecting the questionnaire and tabulating the data, the data was analyzed using the statistical program (R Program) and the results showed a significant and clear impact of the Corona virus on income, especially among the working classes. And with limited income, as well as on the psychological state